O estágio na formação inicial do professor de educação infantil no Curso de Pedagogia da Faced/UFC: perspectivas docente e discente - Lima, Tathiane Rodrigues (2018)
The present research presented a discussion about the initial formation of teachers, focusing on the obligatory curricular component Internship in Early Childhood Education (IECE), of the Daytime Pedagogy course of the Faculdade de Educação of the Universidade Federal do Ceará (FACED/UFC). The main objective was to analyze the formative contributions of IECE for the teacher training aiming to work in the first stage of basic education, based on the perspectives of teachers, students and graduates of the FACED/UFC Pedagogy course. Theoretical contributions were made by authors who highlight the need for articulation between theory and practice in the initial formation of teachers such as Formosinho (2009, 2011), Kishimoto (2011), Oliveira-Formosinho (2002, 2011), Ostetto, 2014), Pimenta et al. (2017) and Pimenta and Lima (2010). Based on the qualitative approach, through the characteristics of a case study, the research used as techniques for data construction the application of questionnaires and the conduction of semi-structured interviews. The subjects were three teachers responsible for the curricular component IECE, six students from the Daytime Pedagogy course at FACED/UFC and five students from this course who teach in Early Childhood Education (CE). The analysis of the data revealed that the relationship between theory and practice is a challenge regarding its materialization in the IECE, since most of the subjects realized that in the course of Pedagogy of the FACED/UFC there is a separation between the “theoretician” and the “practical”. Among the contributions of this curricular component for teaching in the CE, the subjects cited the opportune moment to develop a reflexive look, to build knowledge related to teaching in CE, to identify themselves with pedagogical work in the age group from zero to five years, to develop a “Vision of child”, and opportunity to build the “know-how”. The research allowed to understand how the thematic of the internship in the scope of the CE has been treated within the university and made possible reflections on a specific formation for the teaching with small children.